Analisis Perbandingan Budget Link antara Perhitungan dan Pengukuran Fiber Optik di Wilayah Jakarta Utara - Kukuh Аrіѕ Santoso; Rulian Alfath (Ikatan Ahli Informatika Indonesia, 2021)
The application of fiber optic cable as a transmission media in the telecommunications world is one of the solutions to the above problems. Optical fiber as a transmission medium is able to improve the service of data, voice and video communication systems such as an increase in the number of available channels, the availability of a large bandwidth, the ability to transfer data at megabits / second speed, guaranteed confidentiality of data sent, and not disturbed by the influence of waves electromagnetic, lightning or weather. This research method uses data collection and data analysis by calculating and measuring optical fiber loss budget links in the North Jakarta area, interviewing field supervisors, literature studies that support problem solving. The results of this study indicate that the calculation results of optical fiber link loss budget are not far from the measurement results so as to provide a very good signal for customers.